TO THE PROBLEM OF PSYCHOLOGICAL ANALYSIS OF COMPONENTS OF PROFESSIONAL IDENTITY OF STUDENTS - PSYCHOLOGISTS - L.V. Zhikhareva (Освітній вимір, 2011)
The article is about research of becoming of professional identity. Author cites a іегвн formation of each component of professional identity at different stages of their education the institute .